The Effect of Problem-Based Learning (PBL) Model On Mathematical Communication Skills of Junior High School Students – A Meta-Analysis Study - Susanti, Nipa; Juandi, Dadang; Tamur, Maximus (JTAM (Jurnal Teori dan Aplikasi Matematika), 2020)
This study aims to integrate research findings on the effect of the Problem-Based Learning (PBL) model on the mathematical communication skills of junior high school students in Indonesia since 2014. The research method used is a meta-analysis with many samples studied, namely 12 published articles. The sampling technique used was purposive sampling. The effect size transformation is based on the g hedge equation calculated using the Comprehensive Meta-Analysis (CMA) application. Based on the results of the analysis, the combined effect of PBL on mathematical communication skills is 0.791, with the high influence criteria according to the random-effect estimation model. There are four criteria considered, namely, sample size, year of study, source of journal publication, and grade level. The results of the heterogeneity test seen based on the variables studied showed that the effect of the PBL learning model was not significantly different from the three moderator variables in terms of sample size, year of study, and publication journals and very different in terms of grade level. This finding is surprising because the random-effects model, as determined by the heterogeneity test, showed variation between effect sizes. Only one of the four variables causes this variation. Therefore further research is needed, which includes more studies and the characteristics studied to describe it more accurately.